Quality improvement of shunt active power filter with dual parallel topology - A. Rahman, Nurul Izuddin (2009)
The potential of a shunt active power filter (APF) with dual parallel (DP) topology as proposed by Lucian Asiminoaei, Cristian Lascu, Frede Blaabjerg and Ion Boldea in mitigating the harmonics current in a three-phase power system feeding a nonlinear load has been verified by conducting a simulation study using Matlab/Simulink. In the control system of this shunt APF, the harmonic currents and the currents between feedback and feedforward APF from the three-phase line are used as a reference input. The error is the comparison of the reference current and the actual compensating harmonic currents from the power devices. The error produced is used as an input to a PI controller for hysteresis current controller (HCC) to generate the switching signals for the APF. The compensated currents produced from the feedback shunt APF will mitigate the 5th and 7th harmonics while the feedforward shunt APF will mitigate the rest of the harmonics until the 31st order. This project proposed by implementing Fuzzy PI controller as a control strategy, APF generate better compensated harmonic currents to the line when more fuzzy rules are created. The APF with DP topology starts to compensate the harmonic currents at t = 0.4s and the load is change from R in series with L to R in parallel with C or vice versa at t = 0.7s. The Fuzzy PI controller response for the increase or reduce of load is faster besides PI controller to mitigate the harmonic currents. Fuzzy PI controller takes less than 0.1s to isolate the harmonics currents, but PI controller take more than 0.1s to isolate the harmonic currents. The total harmonic distortion (THD) when used Fuzzy PI controller is lower compared to PI controller.